Exploring the Cultural Philosophy of Red Kebaya Through Sundanese Song Lyrics - Srihilmawati, Rostika; M. Arinal Rahman; Ciptro Handrianto (International Journal of Language and Culture, 2023)
The kebaya, when analyzed through the lens of song lyrics, emerges not just as a garment but as enveloping the transmission of ancestral wisdom, embodying a cultural philosophy that has the potential to enrich and guide contemporary lives. This research endeavors to bridge this knowledge gap by unraveling its philosophical values embedded in Sundanese song lyrics. The research is rooted in the philosophy of science, rationalism, empiricism, and scientific methods. The research uncovers a complex interplay of positive and negative values, symbolic meanings, and cultural contexts. The analysis underscores the interconnectedness of color symbolism, historical context, and cultural expressions in shaping the philosophical values associated with traditional attire in song lyrics. In contrast, the analysis uncovered a negative correlation between the red kebaya and depicted wounds or heartache in the song lyrics. The analysis highlights the importance of considering attire as symbolic elements within cultural expressions, moving beyond idealizations to embrace the complexities and realities of romantic experiences.